Moving through Borders: Ghosts of the Troubles in Jan Carson’s The Fire Starters (2019) and The Last Resort (2021) - Héloïse Lecomte (Études Britanniques Contemporaines, 2025)
The works of Northern Irish writer Jan Carson seem to be haunted by the spectre of the Troubles. In her novel The Fire Starters (2019), she questions the assumption that ‘The Troubles are over now’ (7), blurring any clearly-established limit between past and present. Drawing on the metaphorical meaning of the border that separates and yet binds together Northern Ireland and the Republic of Ireland, Carson’s works cross the line between socio-political realism and magical realism. In her darkly comedic elegy, The Last Resort (2021), the ghost figure blurs the limits between past and present, dream and reality by crossing the border between life and death. As such, it epitomises the persistence of the conflict in living memory. Carson’s work also crosses generic borders by challenging the separation between the short story and the novel in The Last Resort. The chorus-like exploration of post-Troubles life complicates the generic classification of her work. In the light of spectrality studies, this paper analyses the ways in which Carson’s (magical and ghost) stories and her poetics of emotion use the motif of porous borders to movingly (re)define the heritage of the Troubles. Northern Ireland, Jan Carson, care, anxiety, magical realism, myth, liminality